PENGARUH BUDAYA ORGANISASI, KOMPENSASI DAN KEPUASAN KERJATERHADAP KINERJA PEGAWAI - Sudiah Hestianah (El-Idaarah, 2021)
This study aims to determine the effect of organizational culture, compensation and job satisfactionsimultaneously and partially and to determine the most dominant variable on employeeperformance at PT. Bank BRI Syariah Sidoarjo Branch Office. Determination of the sample in thisstudy using random sampling as many as 30 respondents. Data collection was carried out using aquestionnaire that had been tested for validity and reliability. The analysis used is multiple linearregression analysis with the help of the SPSS 18 for windows program. Based on the results of theanalysis it can be concluded that: there is a positive and significant influence of organizationalculture, compensation and job satisfaction simultaneously on the performance of employees at PT.Bank BRI Syariah Sidoarjo Branch Office, that is evidenced by the value of Fcount (16.290) > Ftable(2.98). there is a positive and significant influence of organizational culture, compensation and jobsatisfaction partially on the performance of employee of PT. Bank BRI Syariah Sidoarjo BranchOffice, this is evidenced by the value of tcount of organizational culture (5.938) > ttable (2.055), valueof compensation tcount (4.078) > ttable (2.055) and tcount of job satisfaction (5.058) > ttable (2.055).That the organizational culture is more dominant in the performance of the employee of PT. BankBRI Syariah Sidoarjo Branch Office, this is evidenced by the coefficient of determination oforganizational culture (0.6773) > the coefficient of determination of compensation (0.2294) andthe coefficient of determination of job satisfaction (0.4844).